2004
DOI: 10.1021/jp047421d
|View full text |Cite
|
Sign up to set email alerts
|

Differential Scanning Calorimetry Studies of Clathrate Hydrate Formation

Abstract: Differential scanning calorimetry was applied to investigate the formation of tetrahydrofuran (THF) and cyclopentane (CP) clathrate hydrates. An emulsion technique was developed to determine the hydration number and the enthalpy of CP hydrate dissociation to liquid water and liquid cyclopentane, which were found to be 16.8 ( 0.7 and 82.3 kJ/mol CP, respectively. The hydration number corresponds to the theoretical number of 17 if all of the large cavities in the structure II hydrate are occupied. Experiments wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
93
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 26 publications
9
93
0
Order By: Relevance
“…The Span 80 system (no silica nanoparticles) was used as a reference sample, and the heat of hydrate dissociation from the reference sample shows 260 J g À1 of water, which is in good agreement with a previous result (269 J g À1 of water) reported by Zhang et al [17] As shown in Figure 4A, the second endothermic signal from the CP hydrate dissociation greatly decreases and exhibits an upward shift, thereby implying a reduction of the hydrate amount in the Span 80/particles system. Figure 4B clearly represents the significant inhibition of hydrate formation with the particle-injected samples as the amount of SiNPs increases in the micro-DSC experiments.…”
Section: Resultssupporting
confidence: 90%
“…The Span 80 system (no silica nanoparticles) was used as a reference sample, and the heat of hydrate dissociation from the reference sample shows 260 J g À1 of water, which is in good agreement with a previous result (269 J g À1 of water) reported by Zhang et al [17] As shown in Figure 4A, the second endothermic signal from the CP hydrate dissociation greatly decreases and exhibits an upward shift, thereby implying a reduction of the hydrate amount in the Span 80/particles system. Figure 4B clearly represents the significant inhibition of hydrate formation with the particle-injected samples as the amount of SiNPs increases in the micro-DSC experiments.…”
Section: Resultssupporting
confidence: 90%
“…When the temperature is raised just above the ice melting point, the high contact area between the continuous phase liquid water and the dispersed oil drops promotes nucleation and growth of the cyclopentane hydrate. Zhang et al 41 and Karanjkar et al 31 also observed the formation of hydrate without continuous agitation in their DSC studies of hydrate formation. In our work, the interfacial area between the water and the CyC5 is higher than previous literature reports due to the small size of the CyC5 droplets (~ 5-10 µm in diameter).…”
Section: Formation Of Cyc5mentioning
confidence: 94%
“…In addition, H 2 , C and light hydrocarbon as byproduct were resulted from direct decomposition of methane. Similarly, dissociation enthalpy of cyclopentane hydrate is 82.3 kJ/mol [19] and the reaction of plasma decomposition of cyclopentane hydrate is also shown in Table 30. The direct decomposition of cyclopentane also produced the light hydrocarbon as a byproduct.…”
Section: Resultsmentioning
confidence: 95%